AN ANALYSIS OF THE EFFECTS OF GOVERNMENT POLICY AND THE INVOLVEMENT OF STAKEHOLDERS ON THE PERFORMANCE OF MSMEs - Harini, Sri; Sudarijati, Sudarijati; Arsyad, Apendi (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Matrik: Jurnal Manajemen, Strategi Bisnis dan Kewirausahaan, 2018)
MSMEs have an important role to national development, so it needs to get the attention of government and society. This study aims to assesses the effect of government policy and the involvement of stakeholders (educational institutions, financial institutions, cooperatives, business associations, and NGOs) on the performance of MSMEs.  This study uses a quantitative method, regression and correlation analysis.  Results show that the government has paid special attention to MSMEs through Law No. 20 of 2008, as well as through the Cooperative and MSMEs service office.  Involvement of stakeholders in training, coaching, mentoring, funding, and partnerships have played an important role in improving  MSMEs performance.  MSMEs hope that the government would amend laws and regulations, such as low taxes, simple bureaucracy and easy administrative procedures, would also assist their competitiveness.  MSMEs also needs the sustainable involvement of stakeholders for their empowerment.